ANALISIS PERANAN GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS 2 SD N KARANGREJO 02 SEMARANG - Ina Nur Alimah; Muhammad Prayito; Henry Januar Saputra (STKIP Subang, 2023)
A teacher is a beacon of knowledge and learning. The characteristics of an ideal teacher include both competence and character. An ideal teacher is someone who can impart patience and perseverance. Based on the observations conducted by the researcher during the Field Experience I (PPL I) activities, it was found that the second-grade students at SD Negeri Karangrejo 02 in Semarang still had a low level of academic achievement. This was evident from the evaluation results of the first cycle of teaching practice conducted by the researcher, which indicated that the teaching process in the classroom had not been entirely successful, as reflected in the unstable evaluation scores of the students. This research utilized a qualitative method and was conducted at SD Negeri Karangrejo 02 in Semarang. The research sample consisted of second-grade students at SD Negeri Karangrejo 02 in Semarang. Data collection was carried out through observation and interviews with the second-grade teacher at SD Negeri Karangrejo 02 in Semarang. The data analysis involved data reduction, data display, and conclusion drawing. The results of this research indicate that the role of the teacher in enhancing student achievement includes the stages of opening, core activities, and closure. Additionally, the teacher also plays the roles of motivator, instructor, mentor, and evaluator.